OCA Oracle Database SQL Certified Expert Exam Guide (Exam 1Z0-047) - O'Hearn, Steave; Green, Tim; Lewis, Jack; Walden, Janet (USA The McGraw Hill, 2010)
This exclusive Oracle Press guide covers all of the objectives on the newly created Oracle SQL Expert exam in detail, including control privileges, creating indexes and constraints, altering existing schema objects, creating and querying external tables, and using the advanced SQL features to query and manipulate data within the database. Oracle Database SQL Expert Exam Guide features real-world examples, practice questions, and chapter summaries to help you learn the material. The CD-ROM contains two practice exams and an electronic copy of the book
Indexes
12
Keywords: Database design; Database managent -- Computer Software; Information resources